Infections up to 76 days after stroke increase disability and death - Learoyd, Annastazia; Woodhouse, Lisa J.; Shaw, Laurence; Sprigg, Nikola; Bereczki, Daniel; Berge, Eivind; Caso, Valeria; Christensen, Hanne; Collins, Ronan; Czlonkowska, Anna; El Etribi, Anwar; Farr, Tracy D.; et al. (Springer Verlag, 2017)
Early infection after stroke is associated with a poor outcome. We aimed to determine whether delayed infections (up to 76 days post-stroke) are associated with poor outcome at 90 days. Data came from the international Efficacy of Nitric Oxide Stroke (ENOS, ISRCTN99414122) trial. Post hoc data on infections were obtained from serious adverse events reports between 1 and 76 days following stroke in this large cohort of patients. Regression models accounting for baseline covariates were used to analyse fatalities and functional outcomes (modified Rankin Scale (mRS), Barthel Index, Euro-Qol-5D) at 90 days, in patients with infection compared to those without infection. Of 4011 patients, 242 (6.0%) developed one or more serious infections. Infections were associated with an increased risk of death (p < 0.001) and an increased likelihood of dependency (measured by mRS) compared to those of all other patients (p < 0.001). This remained when only surviving patients were analysed, indicating that the worsening of functional outcome is not due to mortality (p < 0.001). In addition, the timing of the infection after stroke did not alter its detrimental association with fatality (p = 0.14) or functional outcome (p = 0.47). In conclusion, severe poststroke infections, whether occurring early or late after stroke, are associated with an increased risk of death and poorer functional outcome, independent of differences in baseline characteristics or treatment. Not only are strategies needed for reducing the risk of infection immediately after stroke, but also during the first 3 months following a stroke. This study is registered: ISRCTN registry, number ISRCTN99414122, ClinicalTrials.gov Identifier, NCT00989716.